2023
DOI: 10.1093/ehjacc/zuad009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sedation using propofol vs. midazolam in patients admitted to the intensive care unit after extracorporeal cardiopulmonary resuscitation for out-of-hospital cardiac arrest: a multicentre observational study

Abstract: Background Optimal sedation regimens for patients after extracorporeal cardiopulmonary resuscitation (ECPR) remain unclear. This study compared the outcomes of patients who received propofol and midazolam for sedation post-ECPR for out-of-hospital cardiac arrest (OHCA). Methods A retrospective cohort study analysed data from the Study of Advanced life support for Ventricular fibrillation with Extracorporeal circulation in Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…However, the impact of this for patient outcomes appear to be minimal because a study has reported no significant differences in outcomes between propofol and midazolam users among patients treated with ECPR. 49 …”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of this for patient outcomes appear to be minimal because a study has reported no significant differences in outcomes between propofol and midazolam users among patients treated with ECPR. 49 …”
Section: Discussionmentioning
confidence: 99%
“…To examine whether center ECPR volume was associated with survival rate at the time of discharge in patients with OHCA who underwent ECPR, we used a dataset from the SAVE-J II study cohort. The study design has been described in detail elsewhere 8 , 9 . In brief, this cohort derived from a retrospective multicenter study in Japan that included 36 university and community hospitals and enrolled 2,157 consecutive patients with OHCA aged ≥ 18 years who were resuscitated using ECPR between January 1, 2013, and December 31, 2018.…”
Section: Methodsmentioning
confidence: 99%
“…To examine whether center ECPR volume was associated with survival rate at the time of discharge in patients with OHCA who underwent ECPR, we used a dataset from the SAVE-J II study cohort. The study design has been described in detail elsewhere [8,9]. In brief, this cohort derived from a retrospective multicenter study in Japan that included 36 university and community hospitals and enrolled 2,157 consecutive patients with OHCA aged ≥ 18 years who were resuscitated using ECPR between January 1, 2013, andDecember 31, 2018. In the SAVE-J II study, ECPR was de ned as resuscitation with veno-arterial ECMO in patients with refractory cardiac arrest.…”
Section: Study Design and Cohortmentioning
confidence: 99%